Digital-Based Learning Evaluation Model for High School Students - Roza, Ahmad Subhan; Dewi, Asih Fitriana; Wahyuni, Sri (Jurnal Paedagogy, 2024)
This research aims to develop a digital-based learning evaluation model for Senior High School students. This research method used a design research approach with a development study type. This research followed the model developed by Tessmer, which includes the stages of preliminary and formative evaluation. The formative evaluation stage encompasses self-evaluation, prototyping (expert review, one-to-one, and small group), as well as field testing. The data collection techniques for this research involved interviews and questionnaires, with data analysis conducted through both quantitative and qualitative methods. The results of this study indicated that the material validation score was 95.33%, categorized as "very feasible," the language validation score was 93%, also categorized as "very worthy," and the media validation score was 93%, categorized as "very worthy." The results of the response test obtained from the initial trial showed a response from educators of 88% and from students of 87.22%, both categorized as very worthy. Meanwhile, the results from the small group trial indicated a response from educators of 93.89%, also categorized as very worthy, and a response from students of 92.17%, which is again categorized as very worthy. It is clear that Senior High School teachers and students can benefit much from using the digital-based learning evaluation paradigm.